Repertoire and abundance of secreted virulence factors shape the pathogenic capacity of Pseudomonas syringae pv. aptata - Nikolić, Ivan; Glatter, Timo; Ranković, Tamara; Berić, Tanja; Stanković, Slaviša; Diepold, Andreas (Frontiers in Microbiology, 2023)
Pseudomonas syringae pv. aptata is a member of the sugar beet pathobiome and the causative agent of leaf spot disease. Like many pathogenic bacteria, P. syringae relies on the secretion of toxins, which manipulate host-pathogen interactions, to establish and maintain an infection. This study analyzes the secretome of six pathogenic P. syringae pv. aptata strains with different defined virulence capacities in order to identify common and strain-specific features, and correlate the secretome with disease outcome. All strains show a high type III secretion system (T3SS) and type VI secretion system (T6SS) activity under apoplast-like conditions mimicking the infection. Surprisingly, we found that low pathogenic strains show a higher secretion of most T3SS substrates, whereas a distinct subgroup of four effectors was exclusively secreted in medium and high pathogenic strains. Similarly, we detected two T6SS secretion patterns: while one set of proteins was highly secreted in all strains, another subset consisting of known T6SS substrates and previously uncharacterized proteins was exclusively secreted in medium and high virulence strains. Taken together, our data show that P. syringae pathogenicity is correlated with the repertoire and fine-tuning of effector secretion and indicate distinct strategies for establishing virulence of P. syringae pv. aptata in plants.